Life-cycle climate-change impact assessment of enhanced geothermal system plants in the Upper Rhine Valley. (September 2018) - Pratiwi, A.; Ravier, G.; Genter, A.
Highlights: GHG emissions from EGS plants are analysed by employing LCA methodology. Life cycle inventory is constructed using recent data from a geothermal plant in Upper Rhein Valley. Five scenarios are created to represent heat, power and cogeneration configurations. Analyses are performed to identify and compare the impact of each life cycle stage between five scenarios. Approaches to minimize GHG emissions and the associated impacts are analysed. Abstract: In this study the greenhouse gas (GHG) emissions of the Rittershoffen geothermal plant in France – an operating EGS (Enhanced Geothermal System) project developed in the Upper Rhine Valley are analysed and quantified. In this study a similar analysis for the forthcoming EGS in Illkirch Graffenstaden (Strasbourg) is also presented. Life cycle inventory is constructed based on a real project. Five different scenarios comprising a heat plant, power plants and cogeneration plants are developed respecting LCA (Life Cycle Assessment). Contribution of each phase and material type towards GHG emissions is studied using hot spot analysis. In this study some site-specific approaches to potentially reduce of GHG emissions are also assessed. This study is a useful reference towards LCA studies of EGS as it analyses the first EGS utilization for industrial heat.